SUSTAINABLE TOURISM IN SOUTH SULAWESI: DESTINATION ATTRACTIVENESS, SERVICE QUALITY, MARKETING AND COMMUNICATION - Abedneigo Carter Rambulangi; Oktavianus Pasoloran; Otto Randa Payangan; Idrus Taba; Jemi Pabisangan Tahirs (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
This study aims to analyse the influence of destination attractiveness, tourism service quality, marketing strategy, and communication mix on sustainable tourism in South Sulawesi. The research used quantitative methods and collected data through direct and online surveys of 350 domestic tourists visiting key destinations, namely Makassar, Parepare, Tana Toraja, and North Toraja. The sampling technique was purposive with the criteria of tourists who have travel experience at the study locations. Data were analysed using Structural Equation Modelling–Partial Least Squares (SEM-PLS 3.0) to test the measurement and structural models. The results showed that destination attractiveness, service quality, and marketing strategy had a positive and significant influence on sustainable tourism, both directly and through the communication mix. Furthermore, the communication mix was shown to exert a significant influence and to act as a full mediator in the relationship between the independent variables and sustainable tourism. These findings emphasise the importance of integrated communication—including advertising, public relations, social media, and direct marketing—in shaping tourist perceptions and encouraging sustainable tourism practices. In practice, this research provides implications for stakeholders and policymakers in designing tourism development strategies aligned with environmental preservation, culture, and the welfare of local communities in South Sulawesi.